The impact of digital technologies on worker tasks: Do labor policies matter? - Carlos H. L. Corseuil; Jennifer P. Poole; Rita Almeida (Institute for Applied Economic Research (ipea), 2018)
Between 1999 and 2006, Brazilian cities experienced strong growth in the provision of internet services, driven in part by the privatization of the telecommunications industry. A main concern of policymakers is that digital technology replaces routine, manual tasks, displacing lower-skilled workers. In Brazil, stringent labor market institutions exist to protect workers from such shocks, but by increasing labor costs, labor policy may also constrain firms from adjusting the workforce and fully benefiting from technology adoption. We show that digital technology adoption shifted the demand for skills toward an increased use of non-routine and cognitive tasks. Furthermore, and in contrast with labor policy intentions, we show that de facto labor market regulations differentially benefit the most skilled workers, particularly those workers employed in non-routine and cognitive tasks. Our results point to important changes in the future of labor markets in middle-income settings and warn for distortive and unintended consequences of labor market policies.
Keywords: J24; J48; O3; O15; 330; digital technology; skills; labor regulations